2013
DOI: 10.1007/978-3-642-41827-3_65
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of Visual Attentional Patterns for Video Surveillance

Abstract: Abstract. We show that the way people observe video sequences, other than what they observe, is important for the understanding and the prediction of human activities. In this study, we consider 36 surveillance videos, organized in four categories (confront, nothing, fight, play): the videos are observed by 19 people, ten of them are experienced operators and the other nine are novices, and the gaze trajectories of both populations are recorded by an eye tracking device. Due to the proved superior ability of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…For example, Howard et al (2013) found that when monitoring a single scene to detect potentially suspicious events, trained CCTV operators showed greater consistency in fixation location by "knowing what to look for" compared to novices. Using the same dataset as the current study, Roffo et al (2013) found that expert operators are more likely to focus on a small number of interesting regions, sampling them with high frequency. A neuroimaging study, using…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…For example, Howard et al (2013) found that when monitoring a single scene to detect potentially suspicious events, trained CCTV operators showed greater consistency in fixation location by "knowing what to look for" compared to novices. Using the same dataset as the current study, Roffo et al (2013) found that expert operators are more likely to focus on a small number of interesting regions, sampling them with high frequency. A neuroimaging study, using…”
Section: Discussionmentioning
confidence: 77%
“…For example, Howard et al (2013) found that when monitoring a single scene to detect potentially suspicious events, trained CCTV operators showed greater consistency in fixation location by “knowing what to look for” compared to novices. Using the same dataset as the current study, Roffo et al (2013) found that expert operators are more likely to focus on a small number of interesting regions, sampling them with high frequency. A neuroimaging study, using CCTV video stimuli that have some overlap with the current stimuli, also provided converging evidence by demonstrating that a different sample of CCTV operators show increased synchronization of neural responses in certain regions of the brain (i.e., bilateral anterior superior temporal gyrus, left middle temporal gyrus, left ventral striatum, and left inferior parietal lobule) than do novices (Petrini et al, 2014).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation